2007
DOI: 10.1002/mabi.200700020
|View full text |Cite
|
Sign up to set email alerts
|

Uniform Biodegradable Hydrogel Microspheres Fabricated by a Surfactant‐Free Electric‐Field‐Assisted Method

Abstract: Uniform biodegradable hydrogel microspheres (HMS) with precisely controlled size have been fabricated using an electric-field-assisted precision particle fabrication technique. Particle agglomeration was prevented by charging the hydrogel drops and allowing Coulomb repulsion to separate them. As a result, surfactant-free and non-toxic particle fabrication was possible and the resulting microspheres were most suitable for biomedical and food-related applications. Due to the size uniformity, the present HMS may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Gelatin (225 g bloom, BioReagent) nanoparticles were fabricated by an E-PPF method [18] and were cross-linked using 200 mL of 0.125, 0.375, 0.625, and 0.875% w/v glutaraldehyde (GA) (25% aqueous solution, Sigma-Aldrich) solutions at 4 °C for 24 hours, followed by the addition of glycine (Sigma-Aldrich) at room temperature to deactivate the remaining GA [17]. The resulting nanoparticles were washed with DI water and lyophilized.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gelatin (225 g bloom, BioReagent) nanoparticles were fabricated by an E-PPF method [18] and were cross-linked using 200 mL of 0.125, 0.375, 0.625, and 0.875% w/v glutaraldehyde (GA) (25% aqueous solution, Sigma-Aldrich) solutions at 4 °C for 24 hours, followed by the addition of glycine (Sigma-Aldrich) at room temperature to deactivate the remaining GA [17]. The resulting nanoparticles were washed with DI water and lyophilized.…”
Section: Methodsmentioning
confidence: 99%
“…1. The nanoparticle core was fabricated by the Electric Field Assisted Precision Particle Fabrication (E-PPF) method using acidic gelatin, loaded with DOX [17], [18]. The resulting nanospheres were coated with a high-density peptide layer, the hydrolysis of which is catalyzed by Cathepsin D, a specific biomarker protease hypersecreted by breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…The electrostatic atomization is a technique for the atomization of liquid with an electrohydrodynamic (EHD) force, and many studies are reported in recent years . The electrostatic atomization could be classified into three systems as follows: (1) a liquid dispersion into a gas (L/G) system, (2) gas dispersion into a liquid (G/L) system, and (3) a liquid dispersion into a liquid (L/L) system.…”
Section: Introductionmentioning
confidence: 99%
“…According to these reports, chitosan or chitosan‐tripolyphosphate microspheres cross‐linked with glutaraldehyde were prepared with a uniform size of about 5 µm, containing bovine serum albumin or insulin. Finally, Choy et al , reported the chitosan‐based microspheres, which has uniform size of 10–60 µm, could be prepared by using double‐tube nozzle in electric field . Many of recent studies on chitosan‐based nano‐particles for drug delivery were mentioned in a review article …”
Section: Introductionmentioning
confidence: 99%
“…Previously, we reported that mucoadhesive microparticles, when delivered by way of a mannitol-based tablet, resided on the preocular surface longer than the other formulations tested (i.e., aqueous suspensions and tablets with non-mucoadhesive microparticles). 20,21 The prolonged residence time of microparticles was ascribed to the fact that, unlike suspensions, a rapidly dissolving tablet would not expedite tear drainage and, thus, facilitate initial contact between mucoadhesive microparticles and the preocular mucus surface.…”
mentioning
confidence: 99%